THE RIGHT TO EDUCATION OF MEMBERS OF NATIONAL MINORITIES WITH A REVIEW OF NORMATIVE ACTS IN THE REPUBLIC OF SERBIA - Mihailović, Boško (Metodička teorija i praksa, 2025)
The paper analyzes normative acts on national minorities and the right to their education in Serbia, emphasizing the importance of this right for the preservation of cultural and linguistic identity. We will review the legal and institutional framework consisting of the Constitution of the Republic of Serbia, relevant laws and international documents, such as the Framework Convention and the European Charter for Regional or Minority Languages. We will also review relevant legal acts in order to better understand the legal basis for the education of national minorities. The paper points to important segments that must be the subject of future research and analysis in order to improve the position of national minorities in the Republic of Serbia, and to improve and plan in detail the procedures for teaching these social groups. We will highlight challenges in the implementation of the right, such as the lack of teaching materials, staff and infrastructure, and emphasize the need for further improvement of the system for the full implementation of the right to education;